Plastic Pollution and our Moral Responsibility: Lessons from the African Eco-Communitarian Responsibility Approach (Strathmore Law Journal, 2025)
Recently, one typically hears a weighty emphasis on managing plastic waste globally. Thisis due to its detrimental effect on the environment, human health, and the ecosystem. It has been noted that the African continent produces less plastic waste than the global waste landscape. Yet, Africa stands among the most vulnerable continents regarding the harmful effects of plastic pollution. Recent discussions on plastic pollution and its management have often overlooked the African pollution management voice. This paper argues that the Eco-Communitarian Responsibility approach suggests a plausible insight for redefining our moral responsibilities towards plastic pollution in Africa. By exploring the principles of this approach, we can contribute a perspectivebeyond formal law to the global discourse on sustainable environmental practices.The Eco-Communitarian Responsibility approach emphasizes unique values such as interconnectedness and collective responsibility, highlighting the need for diverse perspectives to effectively address plastic pollution in the African context. Using a qualitative research methodology, the article comprehensively reviewed existing literature on plastic pollution in Africa and the principles of the Eco-Communitarian Responsibility approach.The article is structured in five sections: first, the introduction, sets the article's tone. Nextis a discussion of the impact of plastic pollution, highlighting its effects on humans and the ecosystem. The third section examines the current management strategies, exposing the challenges and benefits of each strategy. The fourth section introduces the Eco-Communitarian Responsibility approach and discusses how its principles can informAfrican plastic waste management. This is followed by a conclusion highlighting the implications of the findings and the lessons for future research and policy development.